Synthesis of magnolol-derived bisphosphate for fabrication of bismaleimide resins with intrinsic anti-flammability and smoke suppression. (August 2022) - Guo, Wenwen; Liang, Fuwei; Chen, Shun; Zhang, Diantang; Li, Wenbing; Qian, Kun; Xu, Yang; Fei, Bin
Highlights: Magnolol-derived bisphosphate (MBDPP) was synthesized for fabrication of intrinsically anti-flammable bismaleimide (BMI). BMI thermoset achieved LOI of 35.0% and UL-94 V-0 grade with only 2 wt% of MBDPP. Anti-flammability and smoke suppression performances of the BMI thermosets were significantly enhanced. Abstract: A magnolol-derived bisphosphate (MBDPP) was successfully synthesized from the substitution reaction between magnolol and diphenyl phosphoryl chloride. MBDPP was subsequently applied for the fabrication of intrinsically anti-flammable bismaleimide (BMI) thermosets. The effect of MBDPP on the curing kinetics of BMI systems was investigated by the non-isothermal DSC technology, showing that the addition of MBDPP increased the reaction activation energy of the BMI system owing to the steric hindrance of MBDPP. With only 2 wt% of MBDPP, the BMI thermoset achieved an LOI of 35.0% and UL-94 V-0 grade. Besides, the PHRR, MARHE, THE, TSP and mean SEA of the BMI thermoset with 2 wt% of MBDPP were declined by 26%, 33%, 27%, 34% and 50%, respectively, compared to those of the unmodified BMI. The enhanced anti-flammability and smoke suppression performances of the BMI thermosets were attributed to the formation of an intact, expansive and thermally resistant char layer by the presence of MBDPP. Such a char layer effectively blocked the transportation of combustible degradation products to the flame and the thermal radiation of heat to the polymer matrix, so as to slow down the heat release rate and smoke emission. Graphical abstract: Image, graphical abstract